(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2019)
Software: Software as the starting point for a 3D printing project in medical applications starts with the conversion of DICOM images into STL or similar file formats which allow segmentation, analysis, simulation, calculations and other desired outcomes with clinical relevance. As the medical market is a regulated environment the importance to control the complete 3D printing process is obvious and the need for either a certified software or a validated process chain in total is mandatory. Selection of hardware – material and printer: Each application requires dedicated specifications and the selection of hardware will be chosen wisely. Printing technologies vary from powder bed to resin to filament printing. Medically release materials range from titanium to PA and PEEK and end with medical released resins. The clinical application and the risk classification dictates the material and the technology. Process: The process to design an STL file, to run a printer and store medical grade material, to ensure a quality management and to provide the documentation for audits is certainly a challenge for today`s healthcare system. More and more hospitals step into the role of medical device manufacturers and are confronted with the regulation of MDR and quality management. Market: The hospital market using 3D printing technologies will split into different segments: Some hospitals will consider outsourcing of 3D printing as the ideal solution: shifting responsibilities, investments and risk management to service providers allow the hospital to focus on key competencies. Other hospitals will step into the 3D printing market themselves and take ownership of software, hardware and processes. Every hospital in future will be impacted by 3D printing technologies and will have to choose which direction to enter. MDR with its regulations and uncertainties for companies, notified bodies and hospitals will have an impact in 2020 onwards.